The Neonatal Immune System: A Unique Host-Microbial Interface - Joseph M. Bliss (Frontiers Research Topics, 2018)
Emerging from the protective environment of the uterus, the newborn is exposed to a myriad of microbes, and quickly establishes a complex microbiome that shapes the infant's biology in ways that are only now beginning to come to light. Among these exposures are a number of potential pathogens. The host responses to these pathogens in the neonatal period are unique, reflecting a developing immune system even with delivery at term. Preterm infants are delivered at a time when host defense mechanisms are even less developed and therefore face additional risk. As such, the organisms that cause disease in this period are different from the pathogens that are common in other age groups, or the disease they cause manifests in more severe fashion. Developmental alterations in both innate and adaptive immune responses in neonates have been documented among many cell types and pathways over the last several decades. Contemporary insights into the human immune system and methodologies that allow an "omics" approach to these questions have continued to provide new information regarding the mechanisms that underlie the human neonate as an "immunocompromised host." This Research Topic highlights studies related to this unique host-pathogen interface. Contributions include those related to the innate or adaptive immune system of neonates, their response to microbial colonization or infection, and/or the pathogenesis of microbes causing disease in neonates.